Recent progress in nanobiocatalysis for enzyme immobilization and its application - Min, Kyoungseon; Yoo, Young Je (KOREAN SOC BIOTECHNOLOGY & BIOENGINEERING, 2014)
Recent advances in nanotechnology have provided various nanoscale materials that can be used as support for enzyme immobilization. Nanobiocatalysis integrating the biocatalyst and nanoscale materials is drawing great attention as innovative technology. Nanobiocatalysis could achieve not only a much higher enzyme loading capacity and a significantly enhanced mass transfer efficiency, but also unbelievable stabilization. In this review, we will present and discuss the recent progress in nanobiocatalysis and its applications in the fields of bioelectronics, bioconversion, and proteomics.